Diagnostic office hysteroscopy in a tertiary care centre: a retrospective analysis - Priya, N. Mohna; Lele, Prasad R.; Bhardwaj, Bikram; Naredi, Nikita; Rai, Gunjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Office hysteroscopy is the standard technique for evaluation of intrauterine pathologies in abnormal uterine bleeding, infertility, recurrent pregnancy loss, secondary amenorrhea, post-menopausal bleeding. It is easy to perform, well tolerated by patients and has less complication rates with availability of adequate expertise and equipment. Our aim was to assess the role of diagnostic office hysteroscopy in gynaecology in a referral centre. Methods: A retrospective descriptive study based on hospital records conducted in a government tertiary care centre. Data collected from hospital registers were analysed for common indications, pathology, complications, safety and efficacy of the procedure. Results: Diagnostic office hysteroscopy done on 1624 patients from January 2018 to January 2023 were analysed. Most common indication was infertility. Common pathology seen were intrauterine adhesions, mullerian anomalies and endometrial polyps. Procedure was successful in 94.4% of patients. No major complication observed in any patient. Conclusions: Our findings show that office hysteroscopy is effective, feasible, convenient and safe; in diagnosing various intrauterine pathologies and it is well tolerated by patients. There is no requirement for admission or anesthesia.